AFLP MARKERS BASED DIVERSITY ANALYSIS AMONG WILD RELATIVES OF TOMATO COLLECTED FROM CHHATTISGARH REGIONS OF INDIA - VIKRANT KUMAR SAHU; TOSHI AGRAWAL; A. S. KOTASTHANE (The Bioscan, 2015)
The cultivated Tomato (Solanum lycopersicum) is the second most consumed vegetable worldwide and a well studied crop species in terms of genetics, genomics, and breeding. For the current study wild relatives consisted of cherry and medium sized tomato fruits of 10 tomato genotypes were collected from different regions of Chhattisgarh in order to find out the genetic diversity among these. AFLP analysis revealed that, a total of 2209 reliable polymorphic bands were observed in the 9 AFLP gels varied from 128 to 417, of which only 3 was monomorphic across all 10 genotype. The average no of polymorphic bands present across genotype per primer combination varied from 2.11- 5.48. All the primer combination used in this study has >0.800 PIC value and ranged from 0.813 (ESA14 Vs MSA12) to 0.898 (ESA13 Vs MSA14). The Jaccard’s similarity coefficient for AFLP data set varied from 0.13 to 0.60. The 10 genotype formed 2 major clusters at 13 % similarity level. The lowest similarity (0.13) was between genotypes Raipur cherry and Janjgir long which were the most divergent while the highest similarity (0.72) was found between the genotypes jashpur cherry and Janjgir cripping. This study demonstrated that AFLP markers are effective for obtaining unique fingerprints of, and assessing genetic diversity among, tomato wild relatives.